2002
DOI: 10.1046/j.1471-0528.2002.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Does fear of childbirth during pregnancy predict emergency caesarean section?

Abstract: Objective Caesarean section rates are rising dramatically in the UK. It has been estimated that they have increased from 10% to 22% of all births over 15 years. A Swedish study has suggested that fear of childbirth during pregnancy may increase the risk of emergency caesarean section. The aim of this study is to identify whether fear of childbirth can predict the occurrence of emergency caesarean section in a UK sample. Design A prospective design using between-group comparisons.Setting Sheffield, S. Yorkshire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
140
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 31 publications
24
140
6
Order By: Relevance
“…The two structural regression models differed between the primiparous and the multiparous groups, because women who had an emCS were included in the former [11]. Fear of childbirth factors were considered latent variables in the JW-DEQ versions A and B, which comprised: Fear, Lack of positive anticipation, Isolation and Riskiness [15] [16]. Antenatal fear of childbirth, anxiety, and depression during pregnancy (Time 1), which were determined as exogenous variables, correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The two structural regression models differed between the primiparous and the multiparous groups, because women who had an emCS were included in the former [11]. Fear of childbirth factors were considered latent variables in the JW-DEQ versions A and B, which comprised: Fear, Lack of positive anticipation, Isolation and Riskiness [15] [16]. Antenatal fear of childbirth, anxiety, and depression during pregnancy (Time 1), which were determined as exogenous variables, correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…15 23 On the other hand, other studies reported no such relationships. [24][25][26] One explanation for these inconsistencies could be differences in cultural, social and organisational characteristics between countries. These factors can mediate or exacerbate the effect of anxiety on the birth process and on concomitant interventions.…”
Section: Introductionmentioning
confidence: 99%
“…When measured by the WDEQ-A [21], the prevalence of high levels of childbirth fear (score ≥66) has been consistently reported to be between 24% and 26% [for example, Johnson and Slade [14], Hall et al [16], Zar, Wijma and Wijma [24] – also see Table 1]. …”
Section: Introductionmentioning
confidence: 99%
“…Sweden.K32WDEQ ≥66SwedishAll, Mean 5726%Nullips, Mean 58.626%Multis, Mean 50.326%Johnson, 2002. [14]. UK.K32WDEQ -UKNullips, Mean 65.4-Multis, Mean 58Zar, 2002.…”
Section: Introductionmentioning
confidence: 99%